Python : an introduction to programming - Parker, James (Mercury Learning, 2017)
Following a practical, just-in-time presentation which gives students material as they need it, this guide is designed as a Year One textbook for introduction to programming classes or for the novice hobbyist who wants to learn the fundamentals of programming. --